Some Problems in Market Distribution - Shaw, A. W. (Quarterly Journal of Economics, 1912)
Lack of systematic study of market distribution. Emphasis on production explained by economic causes. Importance of a better organization of market distribution, 703. — Complexity of the problem facing the distributer. Consumer's surplus. Bearing on the distributer's problem, 707. — Selling at the market minus, selling at the market, and selling at the market plus, 712. — Social justification of the differentiation of commodities: Importance of trade-marking, 718. — Methods of sale: sale in bulk; sale by sample; sale by description, 721. — Available agencies for selling: middlemen, producers' salesmen, and advertising, direct and general, 723. — Emergence and rise in importance of the middleman. Modern tendency to decrease number of successive middlemen, 725. — Analysis of the functions of the middleman: sharing the risk, transporting the goods, financing the operations, selling or communication of ideas about the goods, and assembling, assorting, and re-shipping. Development of functional middlemen. Advantages of direct selling in some industries. Present day importance of the direct selling in some industries. Present day importance of the middleman, 731. — The producer's salesman as an agency in distribution, 740. — Advertising as an agency in distribution: relation to sale by description; relation to trade-marking; analysis of classes of demand created by advertising, 742. — Social waste in distribution. Practical problem of distributer, 746. — Analysis of market into geographic sections and economic and social strata, 749. — Laboratory study of distribution, 754. — Wide application of such method of study, 758. — Possibility of better organization of distribution, 763.